Peningkatan Hasil Belajar PPKn Materi Perumusan dan Penetapan Pancasila sebagai Dasar Negara melalui Model Pembelajaran Discovery Learning di SMPN 3 Trenggalek - Sumadyani, Tavi Astuti (Jurnal Simki Pedagogia, 2020)
From the observations of researchers as PPKn teachers in class VII, it was found that student learning outcomes were very low. Many students do not complete the PPKn learning. The cause of the problem is that Civics learning is boring because the material is difficult to understand and teachers still often use conventional learning methods and models. This problem also occurs in class VII C where the researcher teaches in it. The purpose of the implementation of this classroom action research is to find out the improvement of Civics learning outcomes in the formulation and determination of Pancasila as the basis of the state through discovery learning learning models in class VII C students in semester 1 of the 2017/2018 academic year at SMPN 3 Trenggalek. The subjects in this classroom action research were class VII C students of SMP Negeri 3 Trenggalek. This research design consists of planning, action, observation and reflection stages. From the results of the implementation of Civics learning starting from the pre-cycle to the implementation of the research cycle I and cycle II, it can be concluded that the application of the discovery learning learning model can improve the Civics learning outcomes for grade VII C students of SMP Negeri 3 Trenggalek Semester 1 of 2017/2018. This can be seen from the increase in the percentage of student learning completeness, namely in the first cycle of 73.33% and in the second cycle it increases again until it reaches 100% (all students complete).